A new species of Europlema Holloway, 1998 from Korea (Lepidoptera: Uraniidae, Epipleminae) - J. C. Sohn (SHILAP, 2022)
A new species of Epipleminae, Europlema koreana Sohn, sp. n. is described from Korea on the basis of 15 specimens in the type series. It is distinguished from a congener, E. nubifasciaria (Leech, 1897) in the wing patterns and the features of the male and female genitalia. Its generic assignment to Europlema Holloway, 1998 is discussed.